2018
DOI: 10.15376/biores.14.1.607-618
|View full text |Cite
|
Sign up to set email alerts
|

Surface and dynamic viscoelastic properties of cork from Quercus variabilis

Abstract: Surface and dynamic viscoelastic properties of the reproduction cork from Quercus variabilis were studied in detail. There were 16 chemical elements in the Q. variabilis cork determined by the energy dispersive spectrometric (EDS) spectrum, and the contents of C and O were the highest. The mean colorimetric parameters L*, a*, and b* were 60.8, 14.0, and 30.6, respectively. The surface contact angles of Quercus variabilis cork were measured using an automatic contact angle meter. Three different types of liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Zhao et al (2013) and Bai et al (2014) reported that the cork of Q. variabilis contained impurities in the tissue of cork, such as lenticels tissue, dark-brown zone, and sclereids. Li et al (2019) reported that the virgin cork and reproduction cork of Q. variabilis showed lenticular channels, sclereids surrounded by dark and hard layers, and a smaller lenticular channel in the reproduction cork than in the virgin cork. Additionally, lenticular channels and sclereids in the dark and hard layers of the reproduction cork were less frequent compared to the virgin cork.…”
Section: Macroscopic Structurementioning
confidence: 98%
“…Zhao et al (2013) and Bai et al (2014) reported that the cork of Q. variabilis contained impurities in the tissue of cork, such as lenticels tissue, dark-brown zone, and sclereids. Li et al (2019) reported that the virgin cork and reproduction cork of Q. variabilis showed lenticular channels, sclereids surrounded by dark and hard layers, and a smaller lenticular channel in the reproduction cork than in the virgin cork. Additionally, lenticular channels and sclereids in the dark and hard layers of the reproduction cork were less frequent compared to the virgin cork.…”
Section: Macroscopic Structurementioning
confidence: 98%